Aplicação de um sistema contábil socioambiental para gestão em saúde : estudo de caso no Instituto da Visão - Abe, Tatiana Camasmie [UNIFESP] (2017)
The society has been recently increasing the pressure on the institutions that do not respect the social, environmental and economic aspects, both in decision-making and internal conduct processes. The so-called sustainable growth is based equally on social, environmental and economic dimensions, bringing a response to social and environmental problems caused over the past years, by strictly economic decisions. As a way to improve and structure decisions and activities, the institutions seek to expand its internal controls and assistance in the management tools. This study aims to demonstrate the relevance and application of Environmental Accounting in Health Care through the partial implementation of the SICOGEA method - Generation 3. The nature of the research is exploratory and descriptive and is characterized as a case study at the Instituto da Visão, using semi-structured interviews. The methodological approach is divided into three stages: the first stage provides a theoretical foundation. The stage consists of the case study, with interviews after the adaptation and structuring of a checklist divided into key groups and subgroups. The stage has compiled the results and a summary plan of environmental management accounting results from SICOGEA application. The result obtained with the partial implementation of the SICOGEA - Generation 3 demonstrated that the institution has a general degree of sustainability of 22.4%, which is considered "weak" by the methodology which means that although there are some initiatives in environmental management area, the institution may be causing damage to the environment. The key groups Human Resources and Services Rendered were the main contributors to the result and those with the lowest performance were Marketing and Accounting.